Sovereign Debt Restructuring and Growth - Forni, Lorenzo (IMF Working Papers; Working Paper ;, 2016)
This paper studies the effect of sovereign debt restructurings with external private creditors on growth during the period 1970-2010. We find that there are bad and good (or not so bad) debt restructurings for growth. While growth generally declines in the aftermath of a sovereign debt restructuring, agreements that allow countries to exit a default spell (final restructurings) are associated with improving growth. The impact can be significant. In general, three years after restructuring, growth is about 5 percent lower compared to countries that did not face restructuring over the same period. The exception is for final restructurings, which result in positive growth in the years immediately after the restructuring. Final restructurings tend to be better for growth because they reduce countries' debt, with the strongest effect for countries that exit restructurings with relatively low debt levels.